Creation of low density starting plasma with small frame antenna at Uragan-3M device - Kozulya, M.M.; Kramskoy, E.D.; Korovin, V.B.; Yevsyukov, A.V.; Lozin, A.V.; Kasilov, A.A.; Grigor’eva, L.I.; Kulaga, A.E.; Maznichenko, S.M.; Mironov, Yu.K.; Romanov, V.S.; Chechkin, V.V. (Вопросы атомной науки и техники, 2015)
Deficient shot-to-shot stability of Uragan-3M discharges makes difficult to reproduce experimental results over the period of experimental session. An efficient way of reducing difference between shots is creation of initial low density plasma before the main discharge to start up. A RF pre-ionization in the same frequency range as that of the main discharge is used in the Uragan-3M torsatron. The pre-ionization provides stable discharges during the whole experimental campaign. The main parameters of the pre-ionization plasma are measured and discussed.